PERIPATHETIC NIGHTMARE PILLAGES THE SOCIOLOGY - Zivkovic, Predrag (Politeia, 2020)
Book review by Ph.D. Nemanja Đukić entitled: Phenomenology of erased space. Six Chapters on Identity, Faculty of Political Science, Banja Luka, 2020.